Winter vomiting disease caused by calicivirus. Issue 8 (August 1979) - Cubitt, W D; McSwiggan, D A; Moore, W
Abstract : The clinical, epidemiological, and virological features of an outbreak of winter vomiting disease among London schoolchildren are described. Evidence is presented to support the view that this epidemic was caused by a human calicivirus, a virus not previously shown to be associated with this disease in man.